The Global Exhaustion of The Rental Economy and The Prerequisites for The Transition to Industry 4.0 - Alexey Sergeevich KHARLANOV; Wenhao SHEN; Maksim Mikhailovich NOVIKOV1; Petr Aleksandrovich KOSTROMIN (Communications of International Proceedings, 2021)
This article discusses the rental economy’s theoretical and practical aspects, in particular, on the example of the Russian Federation’s economy, its potential transformation into a "green economy". A literary review of the relationships among greenhouse gas emissions, energy and the economy’s state is carried out. The concept of the "resource curse" – the "Dutch disease of the economy" and its consequences for national income, exports and unemployment is characterized. Approaches to decarbonization and transition to renewable energy sources by Russian and foreign authors are evaluated. The data on the oil recovery’s degree in the largest Russian fields and its share in the country’s export-oriented economy in the context of a decrease in the population’s real disposable incomes are presented. A number of statistical, factual and scientific materials were analyzed, as well as a quantitative and qualitative assessment of this phenomenon in the Russian economy was given. The main forecasts and trends on the way of the economy’s transition to the NBIC-convergence innovative nature and Industry 4.0, hydrogen energy and the green economy are presented.
Keywords: Rental Economy; Industry 4.0; Hydrogen Energy; Climate Agenda